How mortgage finance affects the urban landscape - Sewin Chan; Andrew Haughwout; Joseph Tracy (Federal Reserve Bank of New York, 2015)
This chapter considers the structure of mortgage finance in the U.S., and its role in shaping patterns of homeownership, the nature of the housing stock, and the organization of residential activity. We start by providing some background on the design features of mortgage contracts that distinguish them from other loans, and that have important implications for issues presented in the rest of the chapter. We then explain how mortgage finance interacts with public policy, particularly tax policy, to influence a household's decision to own or rent, and how shifts in the demand for owner-occupied housing are translated into housing prices and quantities, given the unusual nature of housing supply. We consider the distribution of mortgage credit in terms of access and price, by race, ethnicity, income, and over the lifecycle, with particular attention to the role of recent innovations such as non-prime mortgage securitization and reverse mortgages. The extent of negative equity has been unprecedented in the past decade, and we discuss its impact on strategic default, housing turnover, and housing investment. We describe spatial patterns in foreclosure and summarize the evidence for foreclosure spillovers in urban neighborhoods. Finally, we offer some thoughts on future innovations in mortgage finance.
Keywords: G21; R31; R21; 330; mortgage; cities